Bird communities are more functionally redundant in less disturbed Araucaria forest - Calsavara, Larissa Corsini; Lima, Marcos Robalinho; Bochio, Gabriela Menezes; Medeiros, Hugo Reis [UNESP]; dos Anjos, Luiz (Springer Nature, 2024)
Disturbed forests are increasingly common in tropical regions. Although the conservation value of these habitats has been highlighted, few studies have considered their potential in retaining biodiversity and ecosystem services. Therefore, in this study, we address how different levels of disturbance in Araucaria forests affect bird functional diversity. We used Rapid Ecological Assessment as a method to determine a disturbance gradient in Araucaria forest sites and evaluated how biotic integrity of vegetation was associated with alpha functional diversity (functional richness and functional dispersion). We recorded a total of 112 bird species in the eight Araucaria forest sites. Biotic integrity of vegetation ranged from 33.3 to 51.3. No association was found between functional richness and biotic integrity of vegetation. However, we found a negative association between biotic integrity of vegetation and functional dispersion, which indicates that bird communities in less disturbed forests sites are more functionally redundant than those communities in highly disturbed habitats. Overall, the studied disturbed Araucaria forest sites have great biodiversity value and should be considered in conservation strategies to guarantee bird taxonomic and functional diversity.
Keywords: Atlantic rainforest; Bird functional trait; Functional dispersion; Functional richness